Photobleaching Imprinting Enhanced Background Rejection in Line-Scanning Temporal Focusing Microscopy - Zhuang, Chaowei; Li, Xinyang; Zhang, Yuanlong; Kong, Lingjie; Xie, Hao; Dai, Qionghai (Frontiers in Chemistry, 2020)
Compared to two-photon point-scanning microscopy, two-photon temporal focusing microscopy (2pTFM) provides a parallel high-speed imaging strategy with optical sectioning capability. Owing to out-of-focus fluorescence induced by scattering, 2pTFM suffers deteriorated signal-to-background ratio (SBR) for deep imaging in turbid tissue, Here, we utilized the photobleaching property of fluorophore to eliminate the out-of-focus fluorescence. According to defendant decay rates at different focal position, we extract the focal-plane signal from time-lapse images. We analyzed the theoretical foundations of photobleaching imprinting of the line-scanning temporal focusing microscopy, simulated the implementation for background rejection, and demonstrated the contrast enhancement in MCF-10A human mammary epithelial cells and cleared Thy1-YFP mice brains. More than 50 % of total background light rejection was achieved, providing higher SBR images of the MCF-10A sample and mice brains. The photobleaching imprinting method can be easily adapted to any fluorescence dyes or proteins which may have application in studies involving relatively large and non-transparent organisms.